Expansionary Fiscal Impact on Macroeconomic Conditions; Computable General Equlibrium (Cge) Model Approach - Rita Handayani; Hastina Febriyanti (SEAN Institute, 2023)
The Computable General Equilibrium model is used to build a general balance in the Indonesian economic model, to see the effectiveness of the impact of expansionary fiscal policy implemented by the Government on economic growth, household group income and sectoral employment during the 2019-2021 pandemic period . The PEP -1-1 model is used with static version 2.0 on GAMS 23.5 software with two variables that are simulated as shocks for the model that has been built, both independently and simultaneously. Using expansionary fiscal policy variables, namely social protection and infrastructure development. The results of the expansionary fiscal simulation carried out by the government increased economic growth by 0.03 percent, increasing sectoral labor absorption in 24 economic sectors in Indonesia. The banking sector and other service sectors experienced the highest increase in labor absorption by 8 percent and the air transportation, trade and fisheries sectors. The impact of the decline occurred in the restaurant and air transportation sectors by 9 percent. The income level indicator also saw an increase in the hhk6, hhk3 and hhd 2 groups reaching 0.52-0.21 percent. Meanwhile, the hhk1 household group was the only household group that experienced a decline in household income of 0.01 percent.